Pension generosity and mental wellbeing: The effect of eradicating poverty at old-age - Alexander M. Danzer; Natalia Danzer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper exploits a unique shift in pension generosity to study the effect of eradicating old-age poverty on mental health. Based on a difference-in-differences set-up we show with two independent data sets from Ukraine that greater pension generosity improves subjective well-being and reduces the incidence of diagnosed depressions. Neither more available leisure time, nor higher consumption levels, nor enhanced physical health can explain the empirical mental health improvement. Instead, we suggest that the main channel for the mental health improvement is the reduced reliance on potentially stressful modes of income generation at old age, such as family household transfers, indebtedness and unpaid bills.
Keywords: H55; I10; I38; 330